Involvement of PSMD10, CDK4, and Tumor Suppressors in Development of Intrahepatic Cholangiocarcinoma of Syrian Golden Hamsters Induced by Clonorchis sinensis and N-Nitrosodimethylamine - Uddin, Md. Hafiz; Choi, Min-Ho; Kim, Woo Ho; Jang, Ja-June; Hong, Sung-Tae (PLOS Neglected Tropical Diseases, 2015)
Author Summary Clonorchis sinensis is a helminth parasite and a carcinogenic agent for cholangiocarcinoma (CCA) or bile duct cancer in humans. Though a large and compelling body of evidence suggests an association between C. sinensis and CCA, the mechanism underlying at the genetic/proteomic level is little known. To explore the underlying molecular mechanism we investigated a number of genes/proteins in C. sinensis induced hamster CCA model. Here C. sinensis induced CCA successfully in all hamsters when introduced with N-nitrosodimethylamine. The histopathology confirmed the development of CCA and detected excessive collagen fibers, mucin and cell division related protein. The quantitative PCR analysis showed increased levels of oncogenes PSMD10, CDK4 and decreased level of tumor suppressor gene p53. The western blot analysis observed significant decrease of another tumor suppressor called RB protein. Genes/protein expressions were matched well with the pathological changes of CCA hamster. The present study suggests that oncogenes, PSMD10 and CDK4, and tumor suppressors gene p53 and protein RB, are involved in the carcinogenesis process of C. sinensis induced CCA in hamsters.